The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1074/jbc.274.4.2234
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Stress Signaling Pathways by the End Product of Lipid Peroxidation

Abstract: In the present study, we studied the signal transduction mechanism that is involved in the expression of c-Jun protein evident after exposure of rat liver epithelial RL34 cells to the major end product of oxidized fatty acid metabolism, 4-hydroxy-2-nonenal (HNE). HNE treatment of the cells resulted in depletion of intracellular glutathione (GSH) and in the formation of proteinbound HNE in plasma membrane. In addition, HNE strongly induced intracellular peroxide production, suggesting that HNE exerted oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
162
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 538 publications
(168 citation statements)
references
References 76 publications
4
162
0
2
Order By: Relevance
“…HNE did not inhibit any of these upstream kinases, and in fact, a brief survey indicated that it stimulated the activity of ERK1, ERK2, JNK1, and JNK2 (data not shown). This is consistent with a previous finding of stimulation of p38 kinase activity by HNE (42).…”
Section: Discussionsupporting
confidence: 83%
“…HNE did not inhibit any of these upstream kinases, and in fact, a brief survey indicated that it stimulated the activity of ERK1, ERK2, JNK1, and JNK2 (data not shown). This is consistent with a previous finding of stimulation of p38 kinase activity by HNE (42).…”
Section: Discussionsupporting
confidence: 83%
“…This strengthens the prospect of a mechanism that acts through inhibition of survival signaling rather than stimulation of death signaling. Quercetin has been observed to suppress JNK activity induced by hydrogen peroxide (26, 28) and 4-hydroxy-2-nonenal (27), suggesting that quercetin is able to prevent stress-induced activation of JNK but not basal activation. This agrees with previous investigations where the flavonoids epicatechin, 3Ј-O-methyl epicatechin, and kaempferol inhibited JNK activation by oxidized low density lipoprotein but had no effect on basal JNK phosphorylation (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been observed to induce caspase-3 activation in the malignant cell line HPB-ALL (24), activate caspase-3 and caspase-9, release cytochrome c in HL-60 cells (25), and induce chromatin and nuclear fragmentation in colonic cancer cells (20). On the other hand, quercetin treatment has been shown to suppress the c-Jun N-terminal kinase (JNK) 1 activity and apoptosis induced by hydrogen peroxide (26) and 4-hydroxy-2-nonenal (27). Furthermore, quercetin may evoke anti-apoptotic effects via the suppression of the peroxide-induced JyNK-cJun/AP-1 pathway and the ERK-c-Fos/AP-1 pathway in cultured mesangial cells (28).…”
mentioning
confidence: 99%
“…5) Among the aldehydes generated as the result of membrane lipid peroxidation, HNE can be produced in relatively large concentrations up to 5 mM in cells, and is the most damaging to cells. 3,6) Koster et al also reported that the concentration of HNE in the lipid bilayer of peroxidized microsomes is about 4.5 mM. 7) HNE directly interacts with several amino acid residues of protein, i.e., the sulfhydryl (SH) group of cysteine, the imidazole moiety of histidine and the e-amino group of lysine through a Michael-type nucleophilic addition.…”
mentioning
confidence: 99%